2008
DOI: 10.1111/j.1745-7254.2008.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of prostaglandin E1 and lithium in a rat model of cerebral ischemia1

Abstract: Aim: Heat shock proteins (HSPs) are important regulators of cellular survival and exert neuroprotective effects against cerebral ischemia. Both prostaglandin E1 (PGE1) and lithium have been reported to protect neurons against ischemic injury. The present study was undertaken to examine if lithium could potentiate the neuroprotection of PGE1 against cerebral ischemia, and if the synergetic effects take place at the level of HSPs. Methods: Brain ischemia was induced by a permanent middle cerebral artery occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…In the groups treated with PGE1 or lithium alone, a reduction in infarct volume and improvement of neurological deficits was observed, but a greater reduction in infarct volume and neurological deficits was seen in rats that were given a PGE1(S)+Li mixture (PGE1 22.6 nmol/kg+Li 0.5 mmol/kg). These results suggest that the PGE1+Li mixture might mimic the synergistic combination therapy of PGE1 and lithium reported in the previous study [14] . The suitable molar ratio of PGE1 to lithium for the PGE1+Li mixture was about 4.5×10 -5 :1.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…In the groups treated with PGE1 or lithium alone, a reduction in infarct volume and improvement of neurological deficits was observed, but a greater reduction in infarct volume and neurological deficits was seen in rats that were given a PGE1(S)+Li mixture (PGE1 22.6 nmol/kg+Li 0.5 mmol/kg). These results suggest that the PGE1+Li mixture might mimic the synergistic combination therapy of PGE1 and lithium reported in the previous study [14] . The suitable molar ratio of PGE1 to lithium for the PGE1+Li mixture was about 4.5×10 -5 :1.…”
Section: Discussionmentioning
confidence: 53%
“…Previous work showed that neither PGE1 alone nor a combination of PGE1 with lithium influences the cerebrocortical blood flow of the pMCAO animals [14] . The results in this study were similar.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations